2004
DOI: 10.1007/s00774-004-0519-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytic osteolysis observed in rats to which parathyroid hormone was continuously administered

Abstract: In order to prove osteocytic osteolysis in vivo, human parathyroid hormone (hPTH (1-34), 749 ng/h), or only solvent of the same volume, was continuously administered to 8-month-old rats by an infusion pump for 4 weeks, and then structural changes in osteocytes in the cortical bones of the tibiae were analyzed morphometrically, histologically, and histochemically. Based on contact microradiography (CMR) observations, the osteocyte lacunae in the PTH group tended to be enlarged, compared with those of the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 27 publications
3
91
1
1
Order By: Relevance
“…Bone remodeling by osteoblasts and osteoclasts, although necessary for calcium homeostasis, is costly in terms of metabolic energy and could lead to detrimental alterations in bone structure and strength; an alternative mechanism for calcium homeostasis is through osteocytic activity. Osteocytes have receptors for parathyroid hormone (PTH), the primary regulator of serum calcium levels (Noble and Reeve, 2000), and osteocytes can produce acid phosphatase, a bone demineralization agent, in response to resorptive signals from continuous PTH elevation, which may cause osteocyte lacunar enlargement (Tazawa et al, 2004). This suggests that osteocytes can detect and respond to signals aimed at serum calcium maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone remodeling by osteoblasts and osteoclasts, although necessary for calcium homeostasis, is costly in terms of metabolic energy and could lead to detrimental alterations in bone structure and strength; an alternative mechanism for calcium homeostasis is through osteocytic activity. Osteocytes have receptors for parathyroid hormone (PTH), the primary regulator of serum calcium levels (Noble and Reeve, 2000), and osteocytes can produce acid phosphatase, a bone demineralization agent, in response to resorptive signals from continuous PTH elevation, which may cause osteocyte lacunar enlargement (Tazawa et al, 2004). This suggests that osteocytes can detect and respond to signals aimed at serum calcium maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the fact that bone loss can occur in these animals during hibernation despite the fact that unbalanced osteoclastic activity may not be observed (Nunez et al, 1972;Steinberg et al, 1981;Doty and Nunez, 1985). Though the osteolytic capacity of osteocytes has been questioned in the past (Parfitt, 1977;Marotti, 1981;Boyde and Jones, 1987), recent literature suggests that osteocytes may use their resorptive capacities to modify their local microenvironment for mineral homeostasis (Cullinane, 2002;Tazawa et al, 2004;Lane et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that the osteocyte can affect changes to its local environment (Baylink and Wergedal, 1971;Rubin et al, 2002;Tazawa et al, 2004;Lane et al, 2006). Additional studies have shown similar results with chondrocytes in cartilage (Guilak et al, 1999(Guilak et al, , 2006Alexopolous et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new evidence has been reported (Tazawa et al, 2004) in the long standing debate that osteocytes can alter their lacuna tissue (Parfitt, 1977). In this study, it was shown that in rats treated continuously with human parathyroid hormone (PTH) for 4 weeks exhibited a significant increase in osteocyte lacunar size due to tissue resorption by the osteocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Osteocyte networks in the bone tissue are implicated in regulating the maintenance and mineralization of bone tissue (70,74), through expression of sclerostin, a negative regulator of bone formation (75), as well as in sensing mechanical load in part through sheer stress generated by interstitial fluid moving through the lacuno-canalicular network (76). It has also been suggested that osteocytes participate in mineral homeostasis by resorbing the lacunar walls in which they are embedded (77)(78)(79).…”
Section: Bone Cellsmentioning
confidence: 99%